Implementation Students' Practices in Internalizing the Values of KH Ahmad Dahlan's Moral Education on Junior High Schools - Quisha Noor Maulida; Istanto Istanto (JIE (Journal of Islamic Education), 2025)
Problems of negative adolescent behaviour, such as violence and delinquency are influenced by internal and external factors. Moral education is considered important in overcoming this problem, but in Indonesia, it tends to be less effective because it focuses more on cognitive aspects than affective ones. KH Ahmad Dahlan's concept of moral education values that emphasise aqidah, sharia, and morals is relevant to overcome this problem. This study aims to describe the practice of the value of moral education of KH Ahmad Dahlan at SMP Muhammadiyah 5 Surakarta examine its impact, and provide solutions to the problem of adolescent morality. This study uses a qualitative method with a phenomenological approach to understanding the phenomenon of student behaviour. Data were collected through semi-structured interviews, passive participation observations, and secondary data. The data analysis used the Miles and Huberman interactive analysis method, which tested its validity through source and time triangulation. The results of this study reveal that KH Ahmad Dahlan's moral education teaches the use of reason based on monotheism to produce good behaviour, with a focus on morality towards Allah, himself, family, society, and the state. Its implementation is through programs such as congregational prayers, counselling, parenting seminars, social services, and flag ceremonies. The impact can be seen in students who are more disciplined, independent, caring, and respectful of the country. KH Ahmad Dahlan's moral education, when applied in schools, is able to suppress the problem of juvenile delinquency, and this method will be effective if accompanied by continuous implementation and supervision.